Research on the adsorption of Pb2+ by apatite ore and purified apatite ore - Phuong, Nguyen Thu; Hong, Cao Thi; Nguyen, Thi Thuy; Nguyen, Thi Xuyen; Nguyen, Thi Thom; Pham, Thi Nam; Nguyen, Thi Thu Trang; Do, Thi Hai; Dinh, Thi Mai Thanh (Vietnam Journal of Science and Technology, 2021)
Apatite ore from Lao Cai province (Vietnam) has large reserves and low cost which was purified by a simple chemical method. Apatite ore and purified one were characterized the molecular structure, phase component, specific surface area, element component, and morphology by IR, XRD, BET, EDX, and SEM methods. The IR result shows both materials have functional groups of fluorapatite such as PO43- and F-. XDR and EDX confirm that the main component of the ore is fluorapatite. After purification, the particles are smaller and more uniform with a higher specific surface area (36.62 m2/g compared with 3.76 m2/g of original apatite ore). Two materials were used to adsorb Pb2+ ions in an aqueous solution. The effect of adsorbent mass, pH, Pb2+ initial concentration, and contact time on adsorption efficiency and capacity was evaluated. The study of adsorption kinetics and isothermal adsorption showed that the Pb2+ adsorption process on apatite ore is matched with the pseudo-second-order kinetic model and the Langmuir model. The comparison between the original apatite ore and purified one was also studied. With 0.05 g of absorbent, after 15 minutes, the efficiency of purified ore is 97.47%, much higher compared with the original ore (50%) after 45 minutes.